Computer-Aided Star Shot Analysis for Linac Quality Assurance Testing. (3rd July 2019) - Szalkowski, Gregory A.; Roper, Justin
Abstract: With the increase in the precision of treatments delivered using radiotherapy machines, there has been a corresponding rise in demand for quality assurance tests that can verify the accuracy of these machines. One common test, star shot analysis, evaluates the isocenter stability of a radiotherapy machine using radiosensitive film or the electronic portal imaging device (EPID). This work details the development of an in-house method of automatically processing film and EPID images to conduct quality assurance testing. In contrast to commercially available software that analyzes a composite image star shot with multiple spokes superimposed on a single image, this work investigates a Gaussian peak finding technique while leveraging the EPID to image one spoke at a time. Spoke-by-spoke analysis was used to investigate the effects of opposing angles on composite image star shot analysis and to assess for collimator trajectories with minimal walkout. This revealed that irradiating film using opposing angles can give artificially low variations in the radiation isocenter due to offsetting deviations from the true center and that walkout was not the same for every 180-deg arc for the collimator, implying that some rotation arcs could give less variation during treatment.